Development of Blooket Application as a Digital Worksheet for Reading Recount Text Skills - Silaban, Rani Enjeli; Caroline Angelica Panjaitan; Febri Salsalina Ginting; Revina Theresia Tarigan; Kezia Esterisa Sembiring; Trivana Pinem (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aimed to develop an interactive digital worksheet using Blooket to support senior high school students’ reading skistudentslls on recount texts. Employing the ADDIE development model, this research involved 30 tenth-grade students at SMA Negeri 23 Batam, selected through purposive sampling. Data were collected through need analysis questionnaires, expert validations, and student evaluations. The need analysis revealed high student interest in digital quiz-based media. Validation results showed that material experts rated the product at an average score of 4.00 (very feasible), while media experts gave it 3.60 (feasible). During implementation, student evaluations produced average scores ranging from 4.18 to 4.71 across five aspects: content validity, technical clarity, interactivity, scoring fairness, and reflective feedback. These results indicate that the developed product is highly appropriate to be used as a formative assessment tool in English reading classes, particularly for recount texts.